Extraction of gum from Chia seeds and study of its chemical Composition and its Antibacterial ability - Zainulabdeen Ali Kadhim AL-Zurfi; Laith Fareed Hasan Al-Obaidi (Kufa Journal for Agricultural Sciences)
The current study aimed to extract gum from chia seeds, study its chemical composition, and determine the optimal conditions for extracting gum from seeds, which included (soaking temperature, soaking period, and mixing ratio), as well as studying the inhibitory activity of gum against some types of bacteria that cause food spoilage. The results of the chemical composition of the gum extracted from chia seeds indicated that the gum contained 6.88% protein, 3.12% fat, 5.60% ash, 2.43% moisture and 81.97% carbohydrates. The results of determining the optimal conditions for the production of extracted plant gum showed that the highest yield of gum reached (9.54%) when extracted at a temperature of (30 C ͦ) and a mixing ratio of (1:40) and a soaking time (60 minutes). This treatment differed significantly from the rest of the treatments were at the level of (p < 0.05), while the lowest yield was recorded for the extracted gum (1.30%) at a temperature of (40 C ͦ), mixing ratio (1:20), and at soaking time (120 minutes). The active groups were identified in the plant gum by Fourier Trans Form Infra-red (FTIR) spectroscopy, and it was observed that groups ((OH), ((C-H), (C-O), (C-O-C), (C=O), (COO-) and (H-H) or (C-H) in the gum extracted from chia seeds. The inhibitory activity of the extracted plant gum was also tested against some types of bacteria that cause food spoilage, including Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae, and at different concentrations (200, 300, and 400 )micrograms. The highest inhibition ability of the gum was against Escherichia coli with a diameter of 23 mm and at a concentration of 400 micrograms, while the lowest inhibition ability was against Staphylococcus aureus with a diameter of 14 mm at a concentration of 200 micrograms.